Wild card [large type] - Silver, Elsie (Silver, Elsie. Rose Hill series, 2026)
"Sebastian Rousseau is a grumpy, hot-as-hell fire pilot who is too damn good with his hands. It's the perfect combination. But unfortunately for Gwen, he's also her ex-boyfriend's dad. A chance meeting brought them together, and a missed connection has kept them apart. One year later, a stroke of fate has them living under the same roof-which makes everything between them downright messy. Because even after all this time, he's still the man Gwen thinks about when she falls asleep. The one she can't get over no matter how hard she tries. Bash is working on mending a fragile relationship with his son, and he and Gwen both know acting on these urges would be the ultimate betrayal. But Gwen sees the heat in his eyes. That look of need that never fails to send a shiver down her spine. The mutual longing is borderline unbearable, and the simmering heat between them is downright palpable. They both know there are rules when it comes to situations like this. But then again . . . following the rules has never felt so futile."--